(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Micro finance has proven to be an effective tool for poverty reduction. Microfinance is the provision of financial services to low-income clients, including consumers and the self-employed, who traditionally lack access to banking and related services. More broadly, it is a movement whose object is “a world in which as many poor and near-poor households as possible have permanent access to an appropriate range of high quality financial services, including not just credit but also savings, insurance, and fund transfers.” Those who promote microfinance generally believe that such access will help poor people out of poverty. The dynamic growth of the microfinance industry has been promoted not only by market forces but also by conscious actions of national governments, Non-Governmental Organizations (NGOs) and the donors who view microfinance as an effective tool for eradicating poverty. The powerful push behind this huge and increasing support for microfinance indicated that national economic and social impacts are significant and it needs to be examined more closely. This paper argues that microfinance can be considered an important element for an effective poverty reduction strategy. It shows that access and efficient provision of microcredit can enable the poor to smooth their consumption, manage their risks better, gradually build their assets, develop their micro enterprises, enhance their income earning capacity and enjoy an improved quality of life. Microfinance services can also contribute to the improvement of resource allocation, promotion of markets, and adoption of better technology thus, microfinance helps to promote economic growth and development.